Pattern and Outcome Analysis of Orthopaedic Injuries and Fractures: A Tertiary Care Hospital-Based Study - Mukherjee, Dr Subhankar; Pratim Pal, Dr Partha; Bhattacharya, Dr Gautam; Roy, Dr Sandip Kr; Roy, Dr Rajiv; Mukherjee, Mrs Deboti (International Journal of Innovative Research in Medical Science, 2018)
Background: Management of a patient who has sustained multiple injuries requires specific and reliable methods of evaluation and treatment. The aim of the present study was to assess the functional outcomes of all traumatic (closed)fractures and how all the variables in our study affect the ultimate functional outcome. Materials & Methods: One hundred and thirty five patients were followed up for duration of 24 weeks at 6 weekly intervals with a proper radiograph of the involved region, with requisite number of views for the assessment of fracture union during each visit. Results: The distribution of the age of the study population was, mean 32.06 (SE 1.442) years. Injury to admission interval mean is 9.56 days (SE 0.635), and injury to definitive management interval mean is 19.43days (SE0.999). Most of the fracture sustained was in the shaft of long bones of lower limbs (22.3%) and fractures around the elbow were second most common (21.5%). Most of the patients had no complications (51.9%) but amongst others, stiffness was the most common complication (21.5%). The distribution of fractures is shaft of femur, tibia and fibula is22.3% and hind foot and proximal humerus fractures accounted for 1.5% respectively. Conclusion: Comparing the Injury to definitive management interval, Analysis of Variance (ANOVA) study showed that lesser the interval, the better the outcome and is statistically significant (P < 0.05,F stat=20.273 ).Similar comparison and ANOVA study also revealed excellent outcome in mean of 6.66(95% CI) days of admission to injury interval and poor outcome in mean14.45(95% CI) of the same.